Market Analysis for the Commmercialization of Stevia in Plant and their Derivatives, in the Canton Montalvo-Ecuador - Miranda Burgos, Mercedes (2021)
The present study was conducted in the city of Montalvo, Los Rios province located at 1 ° 47'24.3 '' South latitude and 79 ° 17'15.3 '' West longitude, the objective is determined the demand and feasibility of implementing a local business for the sale of plant and Stevia derivatives in this canton. The methodology used for this study was that of a semi-structured survey, with two components, the first of which are descriptive and referential about of surveyed and the second raising questions to carry out the market analysis of entrepreneurship, for this a sample of the population was evaluated, using a sample formula.  The results obtained, it can be seen that 50% of the surveyed people used sugar as the main sweetener, compared to 13% who use or know about stevia, in addition 66% of surveyed are willing use stevia as sweetener, also a great percentage would buy the product in form of tea or powder. after analyzing the information obtained in the survey, it is concluded that the implementation of the venture is viable.